HPV vaccination and HIV preexposure prophylaxis (PrEP): Missed opportunities for anal cancer prevention among at risk populations - Christopher W. Wheldon (Taylor & Francis Group, 2022)
Gay, bisexual, and other men who have sex with men (GBM), in addition to transgender women who have sex with men (TW), are at disproportionate risk for anal cancer. Anal cancer can be prevented with HPV vaccination, but uptake among adult GBM/TW is low. Targeted HPV vaccination during the clinical management of pre-exposure prophylaxis (PrEP) is an unexplored strategy relevant to these populations. The purpose of this study was (1) to determine the need for HPV vaccination among GBM and transgender women PrEP users and (2) to identify correlates of HPV vaccination among PrEP users. Secondary analysis of the 2020 Pennsylvania LGBT Health Needs Assessment was conducted to estimate prevalence ratios of HPV vaccination among PrEP users. Overall, 43.8% of the sample had initiated HPV vaccination. Vaccine initiation was significantly lower among respondents 27 to 35 (PR = 0.64; 95% CI: 0.49-0.83) and 36 to 45 (PR = 0.38; 95% CI: 0.25-0.58). Respondents who had received Hepatitis A vaccination were significantly more likely to have had initiated HPV vaccination after adjusting for age (aPR = 2.60; 95% CI: 1.75-3.84). Overall, more than half of eligible GBM and TW engaged in PrEP care have not initiated HPV vaccination and represent potential missed opportunities for anal cancer prevention.